2019
DOI: 10.1097/aog.0000000000003579
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gastrointestinal-Type Chemotherapy in Women With Ovarian Mucinous Carcinoma

Abstract: Personal or nonessential information may be redacted at the editor's discretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…First, it compares tumor progression across three mucinous entities: adenoma, borderline, and invasive ovarian cancer. Second, our cohort included 40 of the rare mucinous ovarian neoplasms, which represents a large number of patients compared with other studies 26 27. Lastly, the inclusion of tumors with different grades and the nearly four decades of long-term follow-up enriches the quality of our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…First, it compares tumor progression across three mucinous entities: adenoma, borderline, and invasive ovarian cancer. Second, our cohort included 40 of the rare mucinous ovarian neoplasms, which represents a large number of patients compared with other studies 26 27. Lastly, the inclusion of tumors with different grades and the nearly four decades of long-term follow-up enriches the quality of our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, more than half of the enrolled patients so far were diagnosed with non-gynecologic mucinous carcinoma after the central review by pathologists. Kurnit et al [ 12 ] conducted a retrospective study to estimate whether gastrointestinal-type chemotherapy was associated with improved survival compared with standard gynecologic regimens for ovarian mucinous carcinoma patients. They found that gastrointestinal-type chemotherapy with or without bevacizumab improved survival in patients with ovarian mucinous carcinoma requiring adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These women may derive more benefit from gastrointestinal-type chemotherapy regimens as compared with traditional carboplatin-based regimens. 27 , 28 …”
Section: Primary Treatmentmentioning
confidence: 99%